Lived experiences of successful research students: exploring learning challenges and strategies in their doctoral learning journey / Hamidah Mohd Ismail - Mohd Ismail, Hamidah (2018)
There has been a substantial increase in the number of research students enrolled in public higher learning institutions in Malaysia. Although the increase in number of PhD enrolment seems to support the nation’s aspiration to elevate human capital, the high attrition rate amongst PhD students is quite alarming. Various research efforts have been carried out to investigate this phenomenon; however, most of the studies were focused on supervision. Although supervision is an integral part of doctoral learning, it is also important to acknowledge the role of learning strategies in the success in completing students’ theses. Research findings have reported that effective use of learning strategies enables learners to take responsibility for their own learning, promotes learner autonomy, and positively relates to students’ academic performance. However, little research has systematically examined the learning strategy use of research students and how they carry out their doctoral learning, in which learner autonomy is of paramount importance. Even less is known about the challenges that research students in Malaysia face during their doctoral learning journey and how they cope with these challenges. This study examines the learning challenges that research students experience during their doctoral learning journey and how they overcome the challenges. This qualitative study involved an extensive collection of time- and contextsensitive data and emphasised on giving participants a personal voice. Snowball sampling was used and a total of eight participants were involved in this study. Four stages of data collection generated rich data from lengthy interviews and provided opportunities for re-interviewing the same participants all over again. Three types of interviews were utilised, and necessary steps were taken to ensure trustworthiness was established in this research. Data analyses were executed during the three stages in which the first stage dealt with the data collected from the storytelling. Meanwhile the second stage was concerned with the data of both the storytelling and the stimulated recall interviews; and the last stage carried out comprehensive analyses on the data generated from the three data collection methods. Three broad categories of learning challenges were identified from the findings namely supervision, academic and psychological. Academic challenges were most profound in their learning in which knowledge creation and conceptualization being the most challenging skills whilst psychological issues were the least challenging. The findings of this study suggested that cognitive learning strategies were the most popular choice of learning strategy type used by the participants. The findings had proven that research students’ complex cognitive development and their self-regulation skills were displayed because of their successful transition from dependent learners to independent researchers. This study contributes to the literature of the three areas on which it was established. First, it extends the research on learning strategies to the context of doctoral students’ learning. This research reveals a range of learning strategies that these successful research students used to extend their learner autonomy. Also, systematic examination of the students’ learning strategy uses casts light on the doctoral learning process. Next, this research has introduced a fresh perspective to the literature on doctoral students, which has been dominated by investigation into the supervision process. Lastly, this research provides an in-depth understanding of the learning processes of successful research students studying in Malaysian universities.